2022
DOI: 10.5662/wjm.v12.i4.319
|View full text |Cite
|
Sign up to set email alerts
|

Pain reduction and adverse effects of intravenous metoclopramide for acute migraine attack: A systematic review and meta-analysis of randomized-controlled trials

Abstract: BACKGROUND Metoclopramide may be used to treat people suffering from acute migraine. However, no comprehensive investigation on this issue has been recorded. This review will provide more solid evidence for the use of metoclopramide in treating acute migraine. AIM To compare the efficacy of intravenous metoclopramide with other therapies in migraine attack treatment in an emergency department (ED). METHODS We included randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…These findings could make us conclude that it had nearly the same rate of complications compared with other drugs. Also, other studies supported what we found [ 39 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings could make us conclude that it had nearly the same rate of complications compared with other drugs. Also, other studies supported what we found [ 39 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding headache outcomes, many systematic reviews and meta-analyses proved its ability in decreasing headache scores [ 7 , 39 , 40 ]. This was in line with our results; however, our review included only the randomized controlled trials that investigated the metoclopramide alone without any combinations, besides we investigated different doses of metoclopramide at different times of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the variability in outcomes is the interaction between dexamethasone and metoclopramide. A study by Corbo et al showed lower efficacy of metoclopramide when combined with magnesium sulfate compared to its use alone (14). Although our study did not combine metoclopramide with magnesium sulfate, the observed dampening effect when metoclopramide was combined with dexamethasone suggests a potential interaction that may reduce overall effectiveness.…”
Section: Figure 1 Gender and Age Sunburst Graphcontrasting
confidence: 56%
“…on metoclopramide treatment for acute migraines, which suggests that metoclopramide is not associated with more significant adverse events than other kinds of medications. 22 There is a lack of experimental evidence regarding the possible mechanism of the anti-migraine effects of metoclopramide, but underlying dopamine D2 antagonism and the related decrease in trigeminovascular activation might explain the treatment efficacy of metoclopramide for acute migraines. 23 Dopamine D2 antagonism may be related to extrapyramidal side effects, such as Parkinsonism and acute dystonia.…”
Section: Discussionmentioning
confidence: 99%